Coping with Disease in Multiple Sclerosis Patients : A Concept Analysis - Dehghani, Ali (Bangladesh Journal of Medical Science, 2019)
Background and Objective: Coping with disease can lead to disease recovery and improve quality of life in people living with multiple sclerosis; therefore, correct definition of this concept is essential. Different dimensions of coping have been emphasized in various studies. This study was aimed to define, clarify and analyzing its concept in people with multiple sclerosis. Materials and methods: In this study, analysis was conducted using the hybrid model in three phases. In the theoretical phase, literature on coping with MS was reviewed until 2016. In the field work phase, in-depth interviews were conducted with 11 people with MS. The conventional content analysis was used in two theoretical and field work phases using Graneheim and Lundman stages. Then, the results of two phases were combined in the final analysis phase. Results and Discussion: The literature review in the theoretical phase revealed five features of coping: accepting the current situation, Self-regulation, Self-efficacy, Multi-dimensional, complex and dynamic nature and Maintenance of effect balance. In the field work phase, maintenance and development of human interactions were added to the features of the concept. Conclusion: Considering these characteristics is necessary in planning to improve coping and quality of life for people living with MS. Bangladesh Journal of Medical Science Vol.19(1) 2020 p.64-72